Penerapan Outing Class untuk Meningkatkan Hasil Belajar Siswa Kelas XI SD 65 Parepare - Ahmad Subair (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
One of the learning methods that can be used to increase student motivation and activeness is the outing class method. This method allows students to actively participate in learning, talk about the concepts and values of heroes' struggle, and develop their critical thinking skills. Hero history material is a subject rich in narrative, conflict, and culture, which allows students to understand the importance of nationalism early on. . This research is also expected to provide an understanding of how the learning approach is in accordance with the learning interests of grade VI students of SDN 65 Parepare. This research applied Classroom Action Research (PTK) which was conducted in two rounds. Each round involved Pre-action, Planning, Implementation, and Evaluation stages. By applying the outing class method, there was an increase in student participation and involvement in the learning process. They were more actively involved, and the number of students from 17% increased to 87% after the second cycle was conducted, especially in sharing opinions and playing an active role in the implementation of contextual learning outside the classroom (outing class).